UMPSA offers 44 bachelor’s degree and 8 diploma programmes in various industry-required fields - Naqiah, Puaad (UMPSA, 2025)
KUANTAN, 23 February 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) offers 44 Bachelor’s degree and eight diploma programmes for students in various fields aligned with industry needs. These academic programmes cover engineering, engineering technology, management, applied sciences, and computing.